2021
DOI: 10.3233/jad-201323
|View full text |Cite
|
Sign up to set email alerts
|

Driving Performance and Its Correlation with Neuropsychological Tests in Senior Drivers with Cognitive Impairment in Japan

Abstract: Background: With the rapid aging of the population, the issue of driving by dementia patients has been causing increasing concern worldwide. Objective: To investigate the driving difficulties faced by senior drivers with cognitive impairment and identify the specific neuropsychological test that can reflect specific domains of driving maneuvers. Methods: Senior drivers with cognitive impairment were investigated. Neuropsychological tests and a questionnaire on demographic and driving characteristics were admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
(77 reference statements)
2
8
0
Order By: Relevance
“…Previous studies reported that patients with mild AD performed significantly worse than those with MCI in a simulated driving test. 11,18,19 The results of the current study also indicate that a negative influence on the ability to drive in patients with AD who progressed from aMCI can be detected by a driving simulator. There was a significant negative correlation between reaction time variability in the selective reaction test and the total MMSE scores.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Previous studies reported that patients with mild AD performed significantly worse than those with MCI in a simulated driving test. 11,18,19 The results of the current study also indicate that a negative influence on the ability to drive in patients with AD who progressed from aMCI can be detected by a driving simulator. There was a significant negative correlation between reaction time variability in the selective reaction test and the total MMSE scores.…”
Section: Discussionsupporting
confidence: 58%
“…An increase in simple reaction time in MCI and AD 25 and a positive correlation between slow reaction speed and GM loss in AD 26 have been reported. It has been reported that delayed driving reactions are associated with decreased MMSE scores 11 and increased risk of traffic accidents. 12 A positive correlation has been reported between the variability of performance on neuropsychological tests and GM atrophy in human immunodeficiency virus patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participant scores for Mini‐Mental State Examination (MMSE), trail‐making test (TMT), block design test (BDT), Alzheimer's Disease Assessment Scale–cognitive subscale (ADAS‐Cog), the clock‐drawing test (CDT), and logical memory (LM) I and II (subtests of the Wechsler memory scale‐revised (WMS‐R)) were collected. The details of these neuropsychological tests were described in our previous study 32 …”
Section: Methodsmentioning
confidence: 99%
“…These domains, ranging from attention and memory to visuospatial skills and executive functions, are interlinked with the brain's complex architecture. For instance, attention allows drivers to continuously monitor the road, quickly detect hazards, avoid distractions, and has been shown to correlate with driving performance metrics such as lane keeping and hazard detection times (Khan et al, 2018;Peng et al, 2021;Ross et al, 2014;Uc et al, 2006;Yi et al, 2015). Memory supports learning and retrieving driving knowledge, recognizing routes, and recalling traffic rules (Scott et al, 2023).…”
Section: Introductionmentioning
confidence: 99%